(untitled) (Research, Society and Development, 2022)
Objective: Identifying the relationship between institutional racism and obstetric violence in black women. Methodology: This is an integrative literature review that followed six steps indicated for its implementation: topic selection and elaboration of the guiding question; literature search; data collect; analysis of included studies; discussion of the result and presentation of the integrative review, the research related results were gathered in a systematic and orderly manner. Results: Pointed to the existence of a greater vulnerability of black women in obstetric care, as they are more susceptible to suffering obstetric violence as a result of the institutional racism installed in society, which is a consequence of the country’s slavery history, which remnants to this day.